PENGUJIAN INTERNATIONAL FISHER EFFECT DI NEGARA-NEGARA ASEAN - , Rulliaman Murdani ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study to testing of International Fisher Effect in ASEAN countries was aimed to test the International Fisher Effect in ASEAN countries hold on a long term or short term with the tendency of the nominal interest rate differential offset changes in currency exchange rates. Another aim is to test the International Fisher Effect by the close relationship on a long term between nominal interest rate differential in the ASEAN countries and the United States of America with changes in currency exchange rates of ASEAN countries against the U.S.dollar. Research conducted a study limited to the ASEAN countries are represented by the state of Indonesia, Singapore, and Malaysia with the comparison countries, namely the United States of America. Data used in this study is the data monthly nominal interest rate and the monthly nominal exchange rate against the U.S. dollar for 12 years from January 2000 until December 2011. Engel Granger method with steps, test stationarity of data with the Augmented Dickey-Fuller test, Engel Granger cointegration test, and Error Correction Model test (ECM) used in this study to test the hypothesis. The results suggest the hypothesis that there is nominal interest rate differential between the ASEAN countries are represented Indonesia, Singapore, and Malaysia to the United States offset changes in currency exchange rates is not proven. Another hypothesis is proven that there is a close relationship the long-term between nominal interest rate differential with changes in currency exchange rates as between the two variables tested cointegration occurs.